Partial-breast irradiation versus whole-breast radiotherapy for early breast cancer: A systematic review and update meta-analysis - Viani, Gustavo Arruda (2020)
Purpose: The purpose of this study was to compare the treatment outcomes of partial-breast irradiation (PBI) versus whole-breast radiotherapy (WBRT) in early breast cancer. Methods and Materials: Eligible randomized clinical trials were identified on Medline, Embase, the Cochrane Library, and the proceedings of annual meetings through December 2019. A meta-analysis for local recurrence (LR), overall mortality (OM), and non-breast cancer mortality (NBCM) was conducted. When possible, the outcomes were calculated for 5, 7, and 10 years of followup. A subgroup analysis by PBI technique (brachytherapy [BT], external beam radiotherapy [EBRT], intraoperative radiotherapy [IORT], and mixed) was performed. A p value < 0.05 was considered significant. Results: Eleven randomized clinical trials with a total of 14,436 patients (7186 PBI vs. 7250 WBRT) were included in the meta-analysis. The odds ratio (OR) for LR in 5 y was 1.46 (95% CI 1.15–2, p = 0.024) for PBI. In the subgroup analysis, no significant difference for LR was observed between PBI and WBRT using BT (p = 0.51), EBRT (p = 0.25), or mixed techniques (p = 0.89). The only subgroup with statistical difference was IORT 3.1 (95% CI 1.2–7.6, p = 0.014). No significant difference in LR was observed with 7 and 10 years among the groups. The OM had no difference at 5, 7, and 10 years of followup for any subgroup. A nonsignificant difference was observed comparing PBI with WBRT for NBCM OR = 1.24 (95% CI 0.98–1.57, p = 0.07). The rates of cardiac death, contralateral breast cancer, and development of second tumor were not significant. Conclusions: The LR with PBI is low and similar to WBRT in selected early breast cancer with a longer followup. The subgroup analysis detected a significant difference for LR associated with IORT and no significant difference for BT and EBRT. Our results confirm a nonsignificant difference for OM and NBCM between PBI and WBRT.